2020
DOI: 10.1016/j.csda.2019.106844
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of general-purpose optimization algorithms for finding optimal approximate experimental designs

Abstract: Several common general purpose optimization algorithms are compared for finding A-and D-optimal designs for different types of statistical models of varying complexity, including high dimensional models with five and more factors. The algorithms of interest include exact methods, such as the interior point method, the Nelder-Mead method, the active set method, the sequential quadratic programming, and metaheuristic algorithms, such as particle swarm optimization, simulated annealing and genetic algorithms. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 71 publications
1
16
0
Order By: Relevance
“…These results are consistent with those of previous publications [8], which suggest that deterministic algorithms are more computationally efficient than nature-inspired metaheuristic algorithms and refer to the slow convergence of metaheuristic algorithms.…”
Section: A Convergence Analysissupporting
confidence: 93%
See 2 more Smart Citations
“…These results are consistent with those of previous publications [8], which suggest that deterministic algorithms are more computationally efficient than nature-inspired metaheuristic algorithms and refer to the slow convergence of metaheuristic algorithms.…”
Section: A Convergence Analysissupporting
confidence: 93%
“…The distributions of the distribution of σ parameter estimates by the natureinspired metaheuristics algorithm are presented in Figure 2 for both datasets. According to [8], in a complex optimization problem where there is no theory to find or verify the optimal, if several nature-inspired metaheuristic algorithms with tuned hyperparameters converge to a solution, this solution is most likely the optimal solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [30], the results showed that SA produced better results than tailored heuristic algorithm in solving the job shop scheduling problem. SA has been used in optimal design problems where many researchers consider SA as a tool in the development process of optimal experimental design [35][36][37][38].…”
Section: Advantages Limitations and Applications Of Ss-based Algorithmsmentioning
confidence: 99%
“…During the last three decades, several search algorithms have been proposed and implemented to solve optimization problems in many engineering and industrial applications; Some are exact with mathematical proofs of convergence and others are based on metaheuristics (Garcı´a-Ro´denas et al, 2020). The exact optimization algorithms include sequential quadratic programming (SQP), interior-point methods (IPMs), and the active set method (ASM).…”
Section: Introductionmentioning
confidence: 99%